A Modified Surgical Technique of Fovea-Sparing Internal Limiting Membrane Peeling: Continuous Arc-Shaped Foldback Peeling - Zheng-Gao Xie; Qing-Yi He; Jun Zhu; Wei Du; Jun Tong; Fang Chen (Journal of Ophthalmology)
Purpose. To investigate the efficacy of management of high myopic foveoschisis (MF) with a modified surgical technique of arc-shaped foldback fovea-sparing internal limiting membrane (ILM) peeling. Methods. A 23-gauge vitrectomy was performed in five patients with high MF. A long strip of ILM was peeled at the temporal side of the central fovea. Next, an ILM forceps was used to grasp the outer side of the ILM flap, and it was moved forward slowly from the outside to the paracentral fovea, followed by folding ILM back in an arc-shaped manner and then removing it. The above operations were repeated, and all ILM flaps were removed from the outside to paracentral fovea until a narrow strip of ILM remained. Finally, the narrow strip of ILM was excised using a vitreous cutter. Results. At the patients’ last visits, the foveoschisis almost disappeared completely and the fovea reattached. The central macular thickness statistically decreased from 399.0 ± 96.33 μm preoperatively to 164.60 ± 34.20 μm postoperatively (t = 4.289; P=0.013). The preoperative mean logarithm of the minimum angle of resolution best-corrected visual acuity (1.64 ± 0.65) significantly improved to 0.72 ± 0.18 postoperatively (t = 3.265, P=0.031). The average follow-up time was 11.80 ± 3.35 months (range; 8–16 months). Conclusion. The arc-shaped foldback fovea-sparing ILM peeling technique for high MF is safe and effective.